Characterizing and Comparing Emissions of Dust, Respirable Crystalline Silica, and Volatile Organic Compounds from Natural and Artificial Stones. Issue 2 (31st July 2021) - Hall, Samantha; Stacey, Peter; Pengelly, Ian; Stagg, Stephen; Saunders, John; Hambling, Susan
Abstract: The frequency of cases of accelerated silicosis associated with exposure to dust from processing artificial stones is rapidly increasing globally. Artificial stones are increasingly popular materials, commonly used to fabricate kitchen and bathroom worktops. Artificial stones can contain very high levels of crystalline silica, hence cutting and polishing them without adequate exposure controls represents a significant health risk. The aim of this research was to determine any differences in the emission profiles of dust generated from artificial and natural stones when cutting and polishing. For artificial stones containing resins, the nature of the volatile organic compounds (VOCs) emitted during processing was also investigated. A selection of stones (two natural, two artificial containing resin, and one artificial sintered) were cut and polished inside a large dust tunnel to characterize the emissions produced. The inhalable, thoracic, and respirable mass concentrations of emissions were measured gravimetrically and the amount of crystalline silica in different size fractions was determined by X-ray diffraction. Emissions were viewed using scanning electron microscopy and the particle size distribution was measured using a wide range aerosol spectrometer. VOCs emitted when cutting resin-artificial stones were also sampled. The mass of dust emitted when cutting stones was higher than that emitted when polishing. For each process, the mass of dust generated was similar whether the stone was artificial or natural. The percentage of crystalline silica in bulk stone is likely to be a reasonable, or conservative, estimate of that in stone dust generated by cutting or polishing. Larger particles were produced when cutting compared with when polishing. For each process, normalized particle size distributions were similar whether the stone was artificial or natural. VOCs were released when cutting resin-artificial stones. The higher the level of silica in the bulk material, the higher the level of silica in any dust emissions produced when processing the stone. When working with new stones containing higher levels of silica, existing control measures may need to be adapted and improved in order to achieve adequate control.